Coumarin derivatives as antifungal agents - A review - Mirjana Lončar; Dajana Gašo-Sokač; Maja Molnar (Czech Journal of Food Sciences, 2023)
Coumarins and pyridines are a promising class of naturally occurring bioactive heterocycles with unique physical and chemical properties. Compounds containing the coumarin framework possess a wide range of pharmacological, biological, and physiological activities, which makes them important for application in medicine, the food industry and agriculture. Among all coumarins' properties, it was found that coumarins may prevent fungal growth, depending on substituents linked to the coumarin core. Therefore, many coumarin derivatives have been investigated as potentially powerful agents in preventing and controlling fungal pathogens. This review summarises the latest research on coumarins and their antifungal activity to provide useful information for further developing more efficient coumarin-based fungicides.